Investigating the Efficacy and Experiences With Narrative Exposure Therapy in Severe Mentally Ill Patients With Comorbid Post-traumatic Stress Disorder Receiving Flexible Assertive Community Treatment: A Mixed Methods Study - Mauritz, Maria; Goossens, Peter; Jongedijk, Ruud; Vermeulen, Hester; van Gaal, Betsie (Frontiers in Psychiatry, 2022)
Background Patients with severe mental illness with repeated interpersonal trauma and post-traumatic stress disorder (PTSD) have a negative illness progression. Traumas are often not treated because of their vulnerability. Narrative exposure therapy (NET) is an effective trauma therapy. It is unknown whether NET is effective and tolerable in these patients receiving community mental healthcare. Objectives The objectives of this study are (1) to gain insights into patients’ experiences before, during, and after NET concerning changes in PTSD, dissociative and severe mental ill symptoms, care needs (CAN), quality of life, and global functioning; (2) to identify factors that influence diagnostic changes after NET as compared to patients’ experiences. These insights will help to decide whether NET should be incorporated in usual care for these patients. Design A mixed methods convergent design consists of a grounded theory approach with thematic analysis followed by a merged analysis, comparing quantitative, and qualitative data for each participant and by means of a joint matrix. Participants Adult psychiatric outpatients (age, 21–65) with post-traumatic stress disorder (PTSD) related to repeated interpersonal trauma were indicted for the study. Methods Baseline demographics and clinical characteristics were assessed. Qualitative data were collected 3 months after NET using individual semi-structured in-depth interviews. The merged analysis compared quantitative and qualitative results for each participant. Results Twenty-three outpatients (female, 82%) with a mean age of 49.9 years (SD 9.8) participated in the study. Participants experienced NET as intensive, and most of them tolerated it well. Afterward, eighteen participants perceived less symptoms. Mixed analysis showed substantial congruency between quantitative scores and participants’ perceptions of PTSD, dissociative symptoms, and CAN (Cohen’s kappa > 0.4). Remission of PTSD was associated with sufficient experienced support. Conclusion Outpatients with severe mental illness underwent intensive NET, and most of them tolerate it well. This therapy is clearly efficacious in this group. Clinical Trial Registration [www.ClinicalTrials.gov], identifier [NL5608 (NTR5714)].